N-Chloro-N-alkoxyureas: synthesis, structure and properties - Shtamburg, V. G.; Shishkin, O. V.; Zubatyuk, R. I.; Kravchenko, S. V.; Tsygankov, A. V.; Mazepa, A. V.; Klots, E. A.; Kostyanovsky, R. G. (Elsevier Inc., 2006)
The XRD studies of N-chloro-N-alkoxyureas 1, 2 have revealed the high pyramidality of the amide nitrogen in the O–N–Cl group caused by nO–s*N–Cl anomeric effect, the other sequence of this effect is anionic lability of the chlorine atom; nucleophilic substitution at the nitrogen depends on the N'-substitutent nature: chlorine atoms in ureas 1 and 5 are replaced by outer nucleophile whereas, under the same conditions, ureas 2–4 undergo cyclization into 1-alkoxybenzimidazolin-2-ones 10–12.